Ancient Winds, Waves, and Atmosphere in Gale Crater, Mars, Inferred From Sedimentary Structures and Wave Modeling. Issue 4 (18th April 2022) - Rubin, D. M.; Lapôtre, M. A. G.; Stevens, A. W.; Lamb, M. P.; Fedo, C. M.; Grotzinger, J. P.; Gupta, S.; Stack, K. M.; Vasavada, A. R.; Banham, S. G.; Bryk, A. B.; Caravaca, G.; et al.
Abstract: Wave modeling and analysis of sedimentary structures were used to evaluate whether four examples of symmetrical, reversing, or straight‐crested bedforms in Gale crater sandstones are preserved wave ripples; deposition by waves would demonstrate that the lake was not covered by ice at that time. Wave modeling indicates that regardless of atmospheric density, winds that exceeded the threshold of aeolian sand transport could have generated waves capable of producing nearshore wave ripples in most grain sizes of sand. Reversing 3‐m‐wavelength bedforms in the Kimberley formation are interpreted not as wave ripples but rather as large aeolian ripples that formed in an atmosphere approximately as thin as at present. These exhumed bedforms define many of the ridges at outcrops that appear striated in satellite images. At Kimberley these bedforms demonstrably underlie and therefore predate subaqueous beds, suggesting that a thin atmosphere existed at least temporarily before subaqueous deposition ceased in the crater. The other three candidate wave ripples (Square Top, Hunda, and Voe) are consistent with modeled waves, but other origins cannot be excluded. The predominance of flat‐laminated (non‐rippled) beds in the lacustrine Murray formation suggests that some aspect of the lake was not conducive to formation or preservation of recognizable wave ripples. Water depths may generally have been too deep, lakebed sediment may have been too fine‐grained, the lake may have been smaller than modeled, or the lake may have been covered by ice. Plain Language Summary: Wave modeling and analysis of sedimentary structures were used to evaluate whether ancient lake deposits in Gale crater contain ripples formed by waves on the surface of the lake. Deposition by waves would show that the lake was not covered by ice at that time. Modeling shows that regardless of atmospheric density, winds capable of moving sand on land would generally have been strong enough to form waves that would produce ripples near shore. Large bedforms in the Kimberley formation are interpreted as ripples formed by the wind in an atmosphere similar to that of Mars today. These bedforms underlie and are older than other beds deposited in water, thereby showing that a thin atmosphere existed at least temporarily before deposition in water ceased in the crater. Three other candidate wave ripples are consistent with modeled waves, but other origins are possible. Thick sequences of sedimentary rock in Gale crater are flat‐laminated rather than rippled, suggesting that some aspect of the lake was not favorable for their formation or preservation. Much of the lake may have been too deep or ice‐covered, or the lake may have been smaller than modeled or had sediment too fine to form easily observed ripples. Key Points: Wave modeling was used to test the hypothesis that 4 examples of lithified bedforms observed by the Curiosity rover are wave ripples 3‐m‐wavelegnth bedforms are thin‐atmosphere aeolian ripples formed before the last subaqueous deposition ended in Gale crater Three examples remain viable candidates for wave ripples‐which would indicate a lake that was largely free of ice at time of deposition